2016
DOI: 10.11609/jott.2774.8.12.9467-9472
|View full text |Cite
|
Sign up to set email alerts
|

New records of petiolate potter wasps (Hymenoptera: Vespidae: Eumeninae) from Bhutan

Abstract: 2 6 O c t o b e r 2 0 1 6 | V o l . 8 | N o . 1 2 | P p . 9 4 6 7 -9 4 7 2 1 0 . 1 1 6 0 9 / j o t . 2 7 7 4 . 8 . 1 2 . 9 4 6 7 -9 4 7 2 T h r e a t e n e d T a x a A l l a r fi c l e s p u b l fi s h e d fi n t h e J o u r n a l o f T h r e a t e n e d T a x a a r e r e g fi s t e r e d u n d e r C r e a fi v e C omm o n s A t r fi b u fi o n 4 . 0 I n t e r n afi o n a l L fi c e n s e u n l e s s o t h e rw fi s e m e n fi o n e d . J o T T a l l ow s u n r e s t r fi c t e d u s e o f a r fi c l e s fi n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Zethus Fabricius, 1804, is the most speciose genus of the Vespidae. It consists of 272 valid species, mainly occurring in the pantropical area with most species in the Neotropical region (230 species); the numbers are much lower for the other regions Afrotropical (15), Oriental (26), and Palaearctic (2) (Giordani Soika 1940, Bohart and Stange 1965, Gusenleitner 2011, Carpenter et al 2010, Carpenter and Madl 2011, Nugroho et al 2012, Nidup et al 2016, Nguyen and Carpenter 2016. In addition, Bohart and Stange (1965) reported one undescribed species from Australia.…”
Section: Discussion Of Oriental and Palaearctic Distribution Of Zethumentioning
confidence: 99%
“…Zethus Fabricius, 1804, is the most speciose genus of the Vespidae. It consists of 272 valid species, mainly occurring in the pantropical area with most species in the Neotropical region (230 species); the numbers are much lower for the other regions Afrotropical (15), Oriental (26), and Palaearctic (2) (Giordani Soika 1940, Bohart and Stange 1965, Gusenleitner 2011, Carpenter et al 2010, Carpenter and Madl 2011, Nugroho et al 2012, Nidup et al 2016, Nguyen and Carpenter 2016. In addition, Bohart and Stange (1965) reported one undescribed species from Australia.…”
Section: Discussion Of Oriental and Palaearctic Distribution Of Zethumentioning
confidence: 99%
“…Pareumenes quadrispinosus was reported from the Himalaya by Bingham (1897), and Srinivasan & Kumar (2010) specifically listed it from Bhutan in their distribution list. Nidup et al (2016) reported seven species of petiolate potter wasps from Bhutan with an additional two subspecies, Pareumenes quadrispinosus acutus and Delta pyriforme pyriforme. This, however, is a mere underestimation of the vast diversity and richness of Eumeninae wasps in Bhutan.…”
mentioning
confidence: 99%